Forehead Movement Discrepancies After Botulinum Toxin Injections: A Review of Etiology, Correction, and Prevention. Issue 1 (2nd January 2022) - Walker, Bridget; Hand, Matthew; Chesnut, Cameron
Abstract : BACKGROUND: Forehead rhytides are a popular target for botulinum toxin injections, but neuromodulation of the frontalis can be fraught with complications because of its anatomic complexity and integral role in brow position and expressivity. OBJECTIVE: This article explores common forehead movement discrepancies that can occur after neuromodulation of the frontalis, as well as how to correct and prevent them. METHODS: A review of the literature was conducted and combined with clinical experience to examine underlying forehead anatomy, etiology and correction of forehead movement discrepancies, and important factors to consider before injecting the frontalis with botulinum toxin. RESULTS AND CONCLUSION: Variable anatomy from person to person necessitates an individualized treatment approach to achieve the best cosmetic results and prevent the occurrence of forehead movement discrepancies.